2009
DOI: 10.1111/j.1752-0606.2009.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Goal Direction and Effectiveness, Emotional Maturity, and Nuclear Family Functioning

Abstract: Differentiation of self, a cornerstone concept in Bowen theory, has a profound influence over time on the functioning of the individual and his or her family unit. This 5-year longitudinal study tested this hypothesis with 50 developing nuclear families. The dimensions of differentiation of self that were examined were goal direction and effectiveness and emotional maturity. A qualitative analysis of participants' goals demonstrated that couples with higher functioning developing nuclear families, when compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
0
15
0
5
Order By: Relevance
“…The individuals in this group are comfortable with being in an intimate relationship since they can maintain a well-defined sense of who they are as individuals (Bowen 1978). In Klever's (2009) study, differentiation of self was represented by goal effectiveness and emotional maturity. The results of this study indicated that the goal effectiveness and emotional maturity of couples predicted variation in nuclear family functioning.…”
Section: Differentiationmentioning
confidence: 99%
“…The individuals in this group are comfortable with being in an intimate relationship since they can maintain a well-defined sense of who they are as individuals (Bowen 1978). In Klever's (2009) study, differentiation of self was represented by goal effectiveness and emotional maturity. The results of this study indicated that the goal effectiveness and emotional maturity of couples predicted variation in nuclear family functioning.…”
Section: Differentiationmentioning
confidence: 99%
“…Emotional maturity in an interpersonal dimension is the ability to experience intimacy without loss of individual autonomy (8). The couple's emotional maturity may improve family functioning (9). Other studies have indicated that emotional maturity has a positive impact on life satisfaction (10), marital satisfaction (11), mental health and coping skills (12).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Olson and Russell (2004) gained insight into how quantitative measures of change intersect with clients’ own experiences of therapy by asking clients about their scores on measures of client outcomes. Klever (2009), drawing on Bowen theory, investigated family functioning with interviews and survey data in a longitudinal study and presented material with clear mixing tables in his results section. In an innovative design, Wynne et al.…”
Section: Discussionmentioning
confidence: 99%